IRF5 polymorphism predicts prognosis in patients with systemic sclerosis. Issue 7 (22nd March 2012) - Sharif, Roozbeh; Mayes, Maureen D; Tan, Filemon K; Gorlova, Olga Y; Hummers, Laura Kathleen; Shah, Ami A; Furst, Daniel E; Khanna, Dinesh; Martin, Javier; Bossini-Castillo, Lara; Gonzalez, Emilio B; Ying, Jun; et al.
Abstract : Objective: The first genome-wide association study (GWAS) of systemic sclerosis (SSc) demonstrated three non-major histocompatibility complex (MHC) susceptibility loci. The goal of this study was to investigate the impact of these gene variants on survival and severity of interstitial lung disease (ILD) in SSc. Methods: The authors examined 1443 Caucasian SSc patients enrolled in the G enetics versus E nvironment I n S cleroderma O utcome S tudy (GENISOS) and Scleroderma Family Registry (n = 914 – discovery cohort) and The Johns Hopkins Scleroderma Cohort (n = 529 – replication cohort). Forced vital capacity (FVC)% predicted was used as a surrogate for ILD severity. Five single nucleotide polymorphisms, IRF5 (rs10488631, rs12537284, rs4728142), STAT4 (rs3821236), CD247 (rs2056626) reached genome-wide significance in the SSc-GWAS and were examined in the current study. Results: Overall, 15.5% of the patients had died over the follow-up period of 5.5 years. The IRF5 rs4728142 minor allele was predictive of longer survival in the discovery cohort (p = 0.021) and in the independent replication cohort (p = 0.047) and combined group (HR: 0.75, 95% CI 0.62 to 0.90, p = 0.002). The association of this SNP with survival was independent of age at disease onset, disease type and autoantibody profile (anticentromere and antitopoisomerase antibodies). The minor allele frequency of IRF5 rs4728142 was 49.4%. Moreover, IRF5 rs4728142 minor allele correlated with higher FVC% predicted at enrolment (p = 0.019). Finally, the IRF5 rs4728142 minor allele was associated with lower IRF5 transcript expression in patients and controls (p = 0.016 and p = 0.034, respectively), suggesting that the IRF5, rs4728142 SNP, may be functionally relevant. Conclusion: An SNP in the IRF5 promoter region (rs4728142), associated with lower IRF5 transcript levels, was predictive of longer survival and milder ILD in patients with SSc.